Reconstructions of the past distribution of Testudo graeca mitochondrial lineages in the Middle East and Transcaucasia support multiple refugia since the Last Glacial Maximum. Issue 1 (2021) - Turkozan, Oguz; Karacaoğlu, Çağaşan; Parham, James F.
No abstract available